Looking good : an introduction to industrial designs for small and medium-sized enterprises. (Geneva, Switzerland : World Intellectual Property Organization, 2003)
"This guide focuses on the role of external appearance in helping companies to differentiate their products from those of competitors and for enhancing their brand image."--Publisher's description.
Available both in print and online.
Cover title.
NLJCols20082021
Keywords: Industrial design; Intellectual property (International law); Industrial design; Intellectual property (International law); Designs; Industrial property; Commercial enterprises